2009
DOI: 10.1111/j.1467-9892.2009.00611.x
|View full text |Cite
|
Sign up to set email alerts
|

Testing for a break in persistence under long‐range dependencies

Abstract: Keywords: break in pesistence, long memory, CUSUM of squares based test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 17 publications
2
58
0
Order By: Relevance
“…More details on the asymptotic distribution of R and critical values can be found in Sibbertsen and Kruse (2009). The simulation results therein show that the test is correctly sized for the sample sizes considered here.…”
Section: Monte Carlo Studymentioning
confidence: 92%
See 2 more Smart Citations
“…More details on the asymptotic distribution of R and critical values can be found in Sibbertsen and Kruse (2009). The simulation results therein show that the test is correctly sized for the sample sizes considered here.…”
Section: Monte Carlo Studymentioning
confidence: 92%
“…To this end, we study the behaviour of a CUSUM of squares-based test suggested by Sibbertsen and Kruse (2009 …”
Section: Monte Carlo Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Leybourne et al (2007) consider long memory dynamics and introduce a test for a break from stationary long memory to non-stationary long memory. Their test is improved by Sibbertsen & Kruse (2009), since the results may be distorted when the data-generating process exhibits long memory. They apply the test to U.S. inflation data and find a break in the early 1980s.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, although stationary long-memory models are often employed in practice, there do not exist many tests for the hypothesis of stationarity which include these processes. Berkes et al (2006), Sibbertsen andKruse (2009) andDehling, Rooch, andTaqqu (2013) consider CUSUM and Wilcoxon type tests to discriminate between long-range dependence and one change in mean. A change with respect to the mean is of course only the simplest possible deviation from stationarity and there is particular interest in measuring deviations in the dependency structure over time as well.…”
Section: Introductionmentioning
confidence: 99%